2020
DOI: 10.1029/2020ea001200
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic and Postseismic Crustal Deformation Associated With the 2016 Kumamoto Earthquake Sequence Revealed by PALSAR‐2 Pixel Tracking and InSAR

Abstract: Coseismic and postseismic crustal deformations caused by earthquake episodes are important in understanding the mechanisms of these episodes as well as the fault rheology near an epicentral area. Specifically, interferometric synthetic aperture radar (InSAR) and synthetic aperture radar (SAR) pixel tracking can depict high-resolution crustal deformation fields associated with earthquakes and volcanic activities without installing on-site observation instruments. In this study, we investigate the coseismic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…However, pre-seismic deformation seems to be sufficiently small given that no significant deformation was observed by the GNSS CORS network and no large seismic event occurred. Although ~ 10 cm post-seismic deformation in Kumamoto has been reported in previous studies (Fujiwara et al 2016;Himematsu and Furuya 2020; Hashimoto 2020; Morishita 2021a), the deformed area was mostly limited where large coseismic deformation occurred and, therefore, the impact of the post-seismic deformation is relatively small. All three methods (i.e., InSAR, SBI, and pixel offset) were applied to each data pair and processed using GSISAR software (Tobita 2003;Morishita et al 2018;Morishita 2019Morishita , 2021b.…”
Section: Data Processingmentioning
confidence: 66%
“…However, pre-seismic deformation seems to be sufficiently small given that no significant deformation was observed by the GNSS CORS network and no large seismic event occurred. Although ~ 10 cm post-seismic deformation in Kumamoto has been reported in previous studies (Fujiwara et al 2016;Himematsu and Furuya 2020; Hashimoto 2020; Morishita 2021a), the deformed area was mostly limited where large coseismic deformation occurred and, therefore, the impact of the post-seismic deformation is relatively small. All three methods (i.e., InSAR, SBI, and pixel offset) were applied to each data pair and processed using GSISAR software (Tobita 2003;Morishita et al 2018;Morishita 2019Morishita , 2021b.…”
Section: Data Processingmentioning
confidence: 66%
“…Deformasi permukaan dalam tiga dimensi dapat ditentukan dengan beberapa kombinasi beberapa metode berikut (Hu dkk., 2014) : (1) kombinasi teknik SAR interferometri dengan Offset-Tracking (Himematsu & Furuya, 2020), (2) kombinasi teknik SAR interferometri dengan Multiple Aperture Interferometry (MAI) (Baek & Jung, 2020), (3) Multi-pass offset-tracking (De Michele dkk., 2010). Perlu diketahui bahwa metode MAI dan offsettracking memiliki tingkat presisi dan resolusi spasial yang lebih rendah dibandingkan teknik SAR interferometri (Panuntun, 2022).…”
Section: Pendahuluanunclassified
“…(2017) proposed that the steady‐state viscosity of the lower crust in Central Kyushu (∼2 × 10 19 Pa s) is lower than the surrounding area (∼2 × 10 20 Pa s), and suggested a weak upper mantle in fore arc that may relates to the shallow fluid release in North Kyushu. Himematsu and Furuya (2020) analyzed 2‐year postseismic deformation with interferometric synthetic aperture radar data, and concluded that the complex near‐field deformation requires consideration of multiple postseismic processes, along with potential influences from geological heterogeneous structure. Moore et al.…”
Section: Introductionmentioning
confidence: 99%